MODERN URBAN PLANNING: CONCEPTS TO PRACTICE - Aleksandrovich Vasilev, Stanislav; Sergeevich Zenin, Sergei; Gennadievich Dedkov, Artem (Revista Inclusiones, 2019)
Modern urban planning has a large number of problems associated with the size of cities and the environmental situation in them. The largest cities continue to expand and develop through some administrative processes. These processes can be rather specific and diverse. Almost every city has its historical center and its industrial suburbs, as well as a residential block-of-flats area surrounding the industrial suburbs. As a result, the transport infrastructure is naturally expanding, thus causing damage to the environment and people’s health. To solve this problem, modern urban planning methods should be developed and implemented taking into consideration modern concepts of urban planning. Conventionally, they can be divided into several blocks, such as curbing the influx of new urban residents from rural areas, applying smart city technologies in urban planning, creating zones for restoring people's health in the city, and modernizing the system of administrative and territorial infrastructure.